REDUCTION OF WELL STIMULATION PERIOD AFTER HYDRAULIC FRACTURING - Alexander Evgenievich Verisokin (Наука. Инновации. Технологии, 2022)
Introduction: The problems arising from backflow of proppant, rock particles and non-decom-posed liquid from hydraulic fractures are considered in the paper. The urgency of the research is caused by the necessity of improvement of well stimulation technology after hydrofracturing. The objective of the paper consists in the development of a set of devices for flushing perforation channels and wellbore walls in the perforation interval after hydrofracturing of a formation. Investigation tools and methods: When writing the paper, the methods of comparison and analysis of national and foreign references in petroleum engineering, patents related to application of formation hydrofracturing were used. Results and discussion: The urgency of developing a device for lushing out of perforated intervals is revealed and substantiated. It is shown that solidified viscoelastic particles of gel enter perforation tunnels and stick to their walls and to the wall of a well. Later these zones of gel particles deposits decrease permeability in perforation tunnels. On the basis of the investigations, the author developed a device for well bottomhole clea-nout that reduces stimulation period for the wells with the above described problems arising after hydrofracturing. To increase productivity of such wells it is necessary to lush out them applying the developed device in the mode of the closest approach to the deposition zones. For better particles lifting to the surface, it is proposed to use foam systems produced by a jet pump which is described in the paper. Conclusion. The set of devices for flushing perforation channels and wellbore walls in the perforation interval which allow for multiple decrease of well stimulation period after hydrofracturing is developed. The described devices are protected by the patents of the Russian Federation: patent for invention No 2651869 "A device for clea-nout", application for patent No 2017109500; patent for invention No 2643882 "Jet pump", application for patent No 2017114222.